The Influence of Physical Activity on Inflammatory Markers, Intestinal Microbiota Composition and Disease Activity in Inflammatory Bowel Disease - Jakubczyk, Paulina; Widera, Piotr; Helis, Justyna; Michalik, Maciej; Buczek, Aleksandra; Bigajski, Hubert; Banaś, Aleksandra; Bilczewska, Olga; Janik, Wiktoria; Handschuh, Marta (Quality in Sport, 2025)
Aim of the Study This review investigates the relationship between physical activity and inflammatory bowel disease (IBD), focusing on inflammatory markers, gut microbiota composition, and disease activity. The objective is to examine how exercise intensities influence inflammation, microbial diversity, and patient outcomes for IBD management. Materials and Methods A literature review synthesized peer-reviewed studies from 2010-2024 using PubMed, Scopus, and Embase databases, examining physical activity effects on inflammatory markers, gut microbiota, and clinical outcomes in IBD patients. Inclusion criteria emphasized human studies, excluding research unrelated to IBD or focused on animal models. State of Knowledge Moderate-intensity aerobic and resistance exercises reduce systemic inflammatory markers, (CRP and cytokines) and enhance gut microbiota diversity, increasing anti-inflammatory species. Low-to-moderate intensity activities improve quality of life in IBD patients. Exercise supports intestinal barrier integrity through mucin production and fatty acid synthesis. High-intensity exercise can worsen inflammation, necessitating tailored protocols. Conclusions Physical activity is a promising adjunctive therapy in IBD management. Moderate-intensity programs effectively maintain remission and enhance outcomes. Future research should focus on longitudinal studies, advanced omics technologies, and combined approaches with dietary and pharmacological therapies.